Effectiveness of a Single Education and Counseling Intervention in Reducing Anxiety in Women Undergoing Hysterosalpingography: A Randomized Controlled Trial - Alfredo La Fianza; Carolina Dellafiore; Daniele Travaini; Davide Broglia; Francesca Gambini; Luigia Scudeller; Carmine Tinelli; Edgardo Caverzasi; Natascia Brondino (The Scientific World Journal)
Hysterosalpingography (HSG) is generally considered a stressful and painful procedure; we aimed to evaluate whether a single education and counseling intervention could reduce women’s distress and pain after undergoing HSG for infertility. Patients were randomized into control group (n=108) and intervention group (n=109). All patients filled the following questionnaires before and after HSG: Zung self-rating anxiety scale (Z-SAS), Zung self-rating depression scale (Z-SDS), and an ad hoc questionnaire designed to evaluate HSG procedure knowledge. Pain was scored using a visual analog scale. The intervention consisted in a 45-minute individualised session 48 h before HSG. We observed a reduction of anxiety and depression scores in the intervention arm compared to the control group. After controlling for potential confounding variables, intervention was an independent predictor of the difference of Z-SAS score before and after HSG. This is the first randomised controlled trial to assess the potential effectiveness of a single education and counseling intervention to lower anxiety in a diagnostic setting.